Congenital anomalies in the rural areas of Kolar District of Karnataka - Bilodi, AKS; Gangadhar, MR (Journal of Institute of Medicine Nepal, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Introduction: Congenital Anomalies are the birth defects which may be morphological, biochemical or behavior of all births that has been induced during any stages of pregnancy. Materials and Methods: The objective of the present study is to know the various types of Anomalies the percentages of incidences of Anomalies and to compare and correlate the present study with available literatures. R.L.Jallappa Teaching Hospital of Sri Devraj Urs Medical College, Tamaka, Kolar Karnataka from 15.02.2007-15.07.2007-Five Months Study Results: Sixty anomalies were observed in live births in the Departments of Surgery and fifteen anomalies in Radiology in the above hospital. The age group of malformations were new born to adult age group. They were seen found 73.00% in males and 27% in females. The overall percentages of incidences of Anomalies in the present study were 2.17%.This study was later compared and correlated with earlier workers and with the available literatures. Conclusion: Ultrasound can diagnose most of the congenital anomalies Key words: Surgical Anomalies Still births and Congenital Malformations. Journal of Institute of Medicine, April, 2008; 30:1 55-58 The full text of this paper is available from the Journal of Institute of Medicine website